CEO Duality: A Review and Research Agenda - Krause, Ryan; Semadeni, Matthew; Cannella, Albert A. (Journal of management, 2014)
CEO duality—the practice of a single individual serving as both CEO and board chair—has been the subject of academic interest for more than 20 years. In that time, boards’ use of CEO duality has fluctuated and the scholarly conceptualizations of the phenomenon have become more complex. As such, the need to understand CEO duality has only increased with time. We review and integrate the disparate literature on this topic so that future attempts to study it will benefit from a more complete understanding of the knowledge already produced. We review the demonstrated antecedents and consequences of CEO duality, pointing out that while much work has been done in this area, much remains that we do not understand. Finally, we offer new theoretical, methodological, and contextual directions that researchers could explore to extend knowledge about CEO duality.